Pengelolaan Emosi Pelaku Klitih di Yogyakarta - Yohanes Eka Wahyuntara; Yohanes Heri Widodo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to: (1) Determine the forms of emotions that often appear in perpetrators (2) Determine the emotional management strategies of perpetrators, (3) Determine the causes of emotional management of perpetrators, (4) Determine the impact of emotional management of perpetrators, (5) Determine the obstacles to managing emotions of perpetrators. This type of research uses a mixed methods approach with a convergent design of mixed methods with data collection techniques using interviews with 3 subjects in accordance with the research criteria. The data analysis technique in this study is based on the results of interviews with subjects, data processing processes, data presentation and conclusions. The results of the study showed that the three subjects were less able to determine good emotion management strategies. Based on aspects of emotion management, the three subjects showed an imbalance between the subject and the management of his emotions. As for these aspects, 1) Awareness of feelings and thoughts that arise, 2) Ability to control negative emotions, 3) Change of negative emotions into motivation.